ChemInform Abstract: Rich Non‐Centrosymmetry in a Na—U—Te Oxo‐System Achieved under Extreme Conditions. Issue 29 (June 2016) - Xiao, Bin; Kegler, Philip; Bosbach, Dirk; Alekseev, Evgeny V.
Abstract: Na[(UO2 )Te IV 2 O5 (OH)] (I), Na2 [(UO2 )(Te VI 2 O8 )] (II), Na2 [(UO2 )Te VI O5 ] (III), Na[(UO2 )Te IV 6 O13 (OH)] (IV) are obtained by hot press sintering of e.g. a mixture of (UO2 )(NO3 )2, TeO2, H6 TeO6, and Na2 S2 O4 as Na source and reductant in the ratio U:Te:Na = 1:5:12 (Pt capsule in piston cylinder talc‐Pyrex assembly, 3.5 GPa, 1100 °C, 3 h).